Clinical and electrophysiological characteristics of autosomal recessive axonal Charcot-Marie-Tooth disease (ARCMT2B) that maps to chromosome 19q13.3 - Berghoff, Corinna (2004)
Artículo científico -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 2004. Este documento es privado debido a limitaciones de derechos de autor.